PENGARUH POLA KEMITRAAN TERHADAP KEUNTUNGAN PETERNAK AYAM PEDAGING (Studi FCR dalam Pola Kemitraan pada CV. Taat Mitra Bersinar Tangerang) - Iwan Ridwan; Agus Widodo; Muhi Mukti (The Asia Pacific Journal Of Management Studies, 2020)
Broiler chicken is a business that can improve the welfare of business people, both plasma (breeders), and core (companies). In these efforts, many factors determine the success or failure of business activities, including: feed efficiency as measured by the Feed Convertion Ratio (FCR), mortality rate (mortality), speed of harvest time, and DOC quality.The research was carried out using quantitative methods. The study population is the Feed Convertion Ratio (FCR) data and recorded benefits from July 2017 to June 2018 as many as 32 data obtained from 4 plasma (chicken breeders) and 8 plasma periods of each period. The sample is determined based on purposive sampling technique. Data analysis uses descriptive-inferential analysis.The results showed that: (1) the average value of the Feed Convertion Ratio (FCR) showed very good results, namely less than the FCR Standards set by the company; (2) the profits obtained by Plasma each period are volatile; and (3) there is an effect of the influence of the Feed Convertion Ratio (FCR) on the benefits of broiler breeders in the Partnership Pattern with CV. Taat Mitra Bersinar Tangerang. The effect is inversely proportional. If the Feed Convertion Ratio (FCR) gets smaller, then the benefits of broiler chicken breeders will be even greater, and vice versa.The study concluded that there was an effect of the effect of Feed Convertion Ratio (FCR) on the benefits of broiler breeders in the Partnership Pattern with CV. Taat Mitra Bersinar Tangerang. Furthermore, it is recommended that this study be developed with a larger sample size. It is also recommended to do research with other methods and with factors other than the Feed Convertion Ratio (FCR) factor.